Interval between Intra-Arterial Infusion Chemotherapy and Surgery for Locally Advanced Oral Squamous Cell Carcinoma: Impacts on Effectiveness of Chemotherapy and on Overall Survival. (18th May 2014) - Wu, Chih-Fung; Lee, Chien-Hsing; Hsi, Edward; Chen, Chung-Ho; Tang, Jen-Yang
Abstract : Background. The interval between intra-arterial infusion chemotherapy (IAIC) and surgery was investigated in terms of its effects on survival in patients with locally advanced oral squamous cell carcinoma (OSCC). Methods. This retrospective study analyzed 126 patients who had completed treatment modalities for stage IV OSCC. All patients were followed up for 3 years. Kaplan-Meier and Cox regression methods were used to determine how survival was affected by general factors, primary tumor volume, TNM stage, and duration of neoadjuvant chemotherapy. Results. In 126 patients treated for locally advanced OSCC by preoperative induction IAIC using methotrexate, multivariate analysis of relevant prognostic factors showed that an IAIC duration longer than 90 days was significantly associated with poor prognosis (hazard ratio, 1.77; P = 0.0259 ). Conclusions. Duration of IAIC is a critical factor in the effectiveness of multimodal treatment for locally advanced OSCC. Limiting the induction course to 90 days improves overall survival.